Characteristics of paediatric injuries as predictors of 24-hour disposition from the Emergency Department of a teaching hospital in South western Uganda - Olinga, Daniel; Oyania, Felix; Bagonza, Kenneth; Odakha, Justine Athieno; Balu, Mabiala Constant; Mwanje, William; Flanery, Andrew; Okello, Ambrose; Musau, Evelyn Mwende; Kizito, Prisca Mary (African Journal of Emergency Medicine, 2024)
Background: Paediatric injuries are among the leading causes of morbidity and mortality globally, especially in low-and middle-income countries. We aimed to characterize paediatric injuries as predictors of disposition from Mbarara Regional Referral Hospital Emergency Department (ED) Southwestern Uganda. Methods: This was a prospective cohort study done from 12th December 2022 to 31st March 2023. We described the characteristics of injuries sustained by children and evaluated the predictors of 24-hour disposition from the ED using logistic regression. Results: Of the 160 children followed up,64.4% were male with a median age of 7years, brought in with road traffic accidents (RTAs) (40.6%) and falls (35.6%) as the commonest mechanism of injury. Over half of the patients were tri-aged as yellow (urgent); polytrauma and head injuries were the top injury patterns. The majority (45.6%) of the children were admitted to the inpatient surgical ward. Only1.9% and 5.0% ended up in intensive care unit (ICU) and died (to mortuary), respectively. The median time to disposition was 8 hand 14% stayed in the ED beyond24-hours. Patients who needed more intensive initial treatment, including additional medications or interventions, were significantly more likely to be admitted to the ward (AOR= 5.3, 95%CI: 2.0-13.0, p <0.01). Conclusion: Paediatric injuries were caused mainly by RTAs and presenting with polytrauma and head injuries. Most patients were disposed of to the inpatient surgical ward within 24 h with severe KTS and initial management being strongest predictors of admission. These findings can be used to tailor quick risk stratification and decision-making tools and improve ED disposition of paediatric injuries in Low-and Middle-income countries.
Keywords: 24-hour disposition; Paediatric injuries; Emergency department; Trauma Initial management